The role of rurality and area-level disadvantage in lifestyle risk factors and psychological well-being among cancer survivors: findings from the 2021 NCI HINTS-SEER - Anita M. Kumar; Carrie A. Miller; Reyna Han; D. Jeremy Barsell; Joseph Boyle; Bernard F. Fuemmeler (Cancer Causes & Control, 2026)
Background Rural cancer survivors consistently experience poorer health outcomes than their urban counterparts, yet the interplay between rurality and area-level disadvantage remains understudied. This study examines how rural versus urban residence and neighborhood disadvantage relate to obesity, smoking, and psychological well-being among cancer survivors. Methods Data from 1,062 HINTS-SEER participants across three registries were analyzed. Logistic regression models estimated associations between area-level factors (Social Deprivation Index (SDI) and Areas of Persistent Poverty) and health outcomes, adjusting for individual sociodemographic factors. Analyses accounted for complex survey design using Taylor series linearization. Results Urban residents showed lower odds of obesity compared with their rural counterparts (OR: 0.69; 95% CI: 0.50–0.95). In stratified analyses, area-level social deprivation demonstrated smaller statistically significant associations. Higher deprivation was associated with increased odds of obesity among urban cancer survivors (OR: 1.01; 95% CI: 1.00–1.02) and increased depression/anxiety among rural survivors (OR: 1.02; 95% CI: 1.00–1.04). Across all models, individual-level socioeconomic factors (education, income) showed stronger, more consistent protective associations than area-level indicators. Conclusions and implications Area-level disadvantage was a contributor to rural cancer survivors’ psychological well-being. Individual socioeconomic status remains the dominant determinant of lifestyle and mental health outcomes. Cancer survivors residing in socioeconomically disadvantaged rural areas may benefit from targeted mental health intervention. Future longitudinal research incorporating census tract–level geographic measures and residential histories is needed to clarify the mechanisms linking the geographic and socioeconomic context to survivorship outcomes.